2022
DOI: 10.3390/foods11152235
|View full text |Cite
|
Sign up to set email alerts
|

Brown Algae as Functional Food Source of Fucoxanthin: A Review

Abstract: Fucoxanthin is an algae-specific xanthophyll of aquatic carotenoid. It is prevalent in brown seaweed because it functions as a light-harvesting complex for algal photosynthesis and photoprotection. Its exceptional chemical structure exhibits numerous biological activities that benefit human health. Due to these valuable properties, fucoxanthin’s potential as a potent source for functional food, feed, and medicine is being explored extensively today. This article has thoroughly reviewed the availability and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 209 publications
0
46
0
Order By: Relevance
“…Previously, the methanolic extract of D. dichotoma was tested for its acetylcholine esterase inhibitory effect, which was comparable to that of the F3 fraction in our study, and the results were 17-fold lower than ours [ 93 ]. Alghazwi et al [ 12 ] summarized the macroalgae-derived compounds that are targeting cholinesterase activity and, in our research, loliolide and fucoxanthin have been found in both tested samples, while α-linolenic acid was found only in D. dichotoma sample, as molecules with enzyme inhibitory effects [ 10 , 94 ]. Aly et al [ 95 ] reported the presence of α-linolenic acid and cystoseirol monoacetate, compounds with good binding affinities to the AChE enzyme [ 95 ], in the methanolic fraction of several Cystoseira species, while the same compounds were also determined in this research for the D. dichotoma F3 fraction.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Previously, the methanolic extract of D. dichotoma was tested for its acetylcholine esterase inhibitory effect, which was comparable to that of the F3 fraction in our study, and the results were 17-fold lower than ours [ 93 ]. Alghazwi et al [ 12 ] summarized the macroalgae-derived compounds that are targeting cholinesterase activity and, in our research, loliolide and fucoxanthin have been found in both tested samples, while α-linolenic acid was found only in D. dichotoma sample, as molecules with enzyme inhibitory effects [ 10 , 94 ]. Aly et al [ 95 ] reported the presence of α-linolenic acid and cystoseirol monoacetate, compounds with good binding affinities to the AChE enzyme [ 95 ], in the methanolic fraction of several Cystoseira species, while the same compounds were also determined in this research for the D. dichotoma F3 fraction.…”
Section: Discussionmentioning
confidence: 70%
“…Brown seaweeds also contain a wide variety of pigments, including fucoxanthin, chlorophyll a, chlorophyll c1, chlorophyll c2, β-carotene, and violaxanthin [ 9 ]. Fucoxanthin is a secondary metabolite produced in the chloroplast of brown macroalgae with great biological activities and protective properties for human health [ 10 ]. It has earned attention due to its promising effects in terms of anti-obesity, antidiabetic, and antioxidant activities [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the fucoxanthin has two hydroxyl groups and three hydrogen-bond as well as long hydrocarbons conjugated double bonds. Previous researchers proposed that fucoxanthin, as an effective inhibitor of α-amylase or starch blockers, has the characteristics of degrade the activity of α-amylase and decrease the conversion rate of starch ( 11 , 55 , 56 ). This may be stably present in the binding pocket of α-amylase and hydrophobic interactions between fucoxanthin long hydrocarbons with conjugated double bonds and the residues on the α-amylase ( 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fucoxanthin is a member of the xanthophyll class of carotenoids and is present at high concentrations in the brown algae Saccharina sp. [ 288 , 289 , 290 , 291 ], where it plays a key role in light harvesting and radiation protection [ 291 ].…”
Section: Natural Antioxidants and Their Benefitsmentioning
confidence: 99%